The Origin of Land Plants: A Phylogenomic Perspective - Bojian Zhong; Linhua Sun; David Penny (Evolutionary Bioinformatics, 2015)
Land plants are a natural group, and Charophyte algae are the closest lineages of land plants and have six morphologically diverged groups. The conjugating green algae (Zygnematales) are now suggested to be the extant sister group to land plants, providing the novel understanding for character evolution and early multicellular innovations in land plants. We review recent molecular phylogenetic work on the origin of land plants and discuss some future directions in phylogenomic analyses.